2015
DOI: 10.1007/s00709-015-0859-5
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular mechanisms of gravity perception and signal transduction in plants

Abstract: Gravity is one of the environmental cues that direct plant growth and development. Recent investigations of different gravity signalling pathways have added complexity to how we think gravity is perceived. Particular cells within specific organs or tissues perceive gravity stimulus. Many downstream signalling events transmit the perceived information into subcellular, biochemical, and genomic responses. They are rapid, non-genomic, regulatory, and cell-specific. The chain of events may pass by signalling lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 198 publications
0
15
0
Order By: Relevance
“…In plants, gravitropism involves the perception of gravity and signal transduction cascades that lead to an asymmetric distribution of auxin and differential growth between the upper and lower sides of responding organs (Strohm et al, 2012). Genetic studies in Arabidopsis have identified several genes involved in shoot gravitropism such as SGR genes and PHOSPHOGLUCOMUTASE genes (Hashiguchi et al, 2013(Hashiguchi et al, , 2014Kim et al, 2016;Kolesnikov et al, 2016). Although other studies have used "omics" techniques and identified gravitropism-related genes or proteins in several species (Moseyko et al, 2002;Kimbrough et al, 2004;Hu et al, 2013Hu et al, , 2015Schenck et al, 2013;Taniguchi et al, 2014;Gerttula et al, 2015;Schüler et al, 2015), the direct link between tiller or branch angle and gravitropism has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…In plants, gravitropism involves the perception of gravity and signal transduction cascades that lead to an asymmetric distribution of auxin and differential growth between the upper and lower sides of responding organs (Strohm et al, 2012). Genetic studies in Arabidopsis have identified several genes involved in shoot gravitropism such as SGR genes and PHOSPHOGLUCOMUTASE genes (Hashiguchi et al, 2013(Hashiguchi et al, , 2014Kim et al, 2016;Kolesnikov et al, 2016). Although other studies have used "omics" techniques and identified gravitropism-related genes or proteins in several species (Moseyko et al, 2002;Kimbrough et al, 2004;Hu et al, 2013Hu et al, , 2015Schenck et al, 2013;Taniguchi et al, 2014;Gerttula et al, 2015;Schüler et al, 2015), the direct link between tiller or branch angle and gravitropism has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most commonly observed of these movements is gravitropism, wherein plant shoots perceive the direction of gravity and regulate their growth to achieve a steady orientation with respect to gravity [2][3][4][5][6][7][8]. The perception of gravity occurs within specialized cells called statocytes through the sedimentation of intracellular statoliths [5,8,9] onto sensory structures. This mechanical signal leads to a differential growth across the cross section of a shoot and thence active (sentient) bending of the respective organ [5][6][7][8]10].…”
Section: Introductionmentioning
confidence: 99%
“…The transduction of the gravity signal on which its biologic effects rely on is currently under investigation 28,29 . Extracellular mechanic stimuli, capable to modulate cell metabolism and mitochondria, have been described primarily in plant cells 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…The transduction of the gravity signal on which its biologic effects rely on is currently under investigation 28,29 . Extracellular mechanic stimuli, capable to modulate cell metabolism and mitochondria, have been described primarily in plant cells 28,29 . In this contest the sensorial apparatus has been identified in membrane receptors, cytoskeletal, and intracellular messengers linked to the modulation of metabolic enzymes 28,29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation